The Issue Of Divorce And Gender Justice Under Personal Law In India (Journal of Namibian Studies : History Politics Culture, 2023)
The issue of divorce and gender justice under personal law in India highlights the complexities surrounding gender equality in marital dissolution within India's pluralistic legal framework. Personal laws, governed by religious customs, regulate divorce rights for various communities, leading to differential treatment based on religious affiliations. While some personal laws have been reformed to enhance gender equality, others continue to uphold patriarchal norms, disproportionately impacting women. The Hindu Marriage Act, the Muslim Personal Law (Shariat) Application Act, and the Parsi Marriage and Divorce Act, among others, each outline unique divorce processes and grounds, reflecting religious principles. However, these laws often restrict women’s agency, placing them at a disadvantage in areas such as alimony, child custody, and remarriage. Notably, recent judicial interventions, including the Supreme Court's judgment in the ShayaraBano case, which declared the practice of triple talaq unconstitutional, have prompted national discourse on the need for a uniform civil code (UCC) that ensures gender-neutral divorce laws. Yet, the move towards a UCC is contested, as it raises concerns about eroding cultural diversity and religious autonomy. Amidst these debates, feminist legal scholars and activists advocate for reforms within personal laws to prioritize gender justice without sacrificing cultural integrity. The challenge lies in balancing the principles of secularism and gender equality while respecting religious freedoms, ensuring that divorce laws foster justice and empowerment for both genders. This paper explores the intersection of divorce, gender justice, and personal laws in India, examining the implications of ongoing legal reforms and the prospects for achieving equitable and inclusive divorce regulations across communities.